Analisis Proses Festival Nampaling Di Desa Cikalong Kecamatan Sidamulih Kabupaten Pangandaran - Khoerunnisa, Dinda (Jurnal Ilmu Sosial, Humaniora dan Seni, 2025)
The Nampaling Festival is one of the traditions in Cikalong Village carried out by farmers when the harvest season arrives. The Nampaling procession is carried out once a year in September. The Nampaling Festival is one of the traditions as a symbol that describes a community with a livelihood as farmers who are able to process all kinds of natural products to be used as a tradition and culture as a tourist village attraction. The author took this discussion using a qualitative research method with a case study approach through audio-visuals that are widely displayed by journalists on one of the social media. The Nampaling Festival has a different attraction to be studied so that the results can be useful to help efforts to trace the writing in preserving this culture